MULTIDISIPLINER DALAM PEMBELAJARAN IPS - Yulia Tri Samiha (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
The scientific method consists of a series of activities which include: the introduction and formulation of the problem, gathering relevant information, formulating a hypothesis, experimentation and publication or dissemination of scientific informasi.Revolusi is a process of transition from the old paradigm of the new keparadignia. With this paradigm shift perspective scientists to determine the problem, define the methods and techniques, and drawing conclusions on the fact alarn will be different than before. Learning from criticism that was developed by the scientific revolution of Popper and Thomas Kuhn, a positive attitude towards rejection and learn as much as possible of the rejection, we should mainly engaged in research, education, and academia should be ready in criticism and too ready to criticize. Besides learning from the rejection was not a bad thing, but it will spur us to produce better. Here we will be tested, if we are prepared to dissent, dissent is not something that is forbidden, but it is a blessing. Says a proverb, a clash that opinion would sprinkle the truth, as long as the goal is not just disagree, but to work together to find the truth.